(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
One of India’s most rapidly expanding sectors in recent years has been retail. The main aim of the study is to Organizational retail customers’ perceptions of the influence of service quality features on their satisfaction and loyalty. The present investigation is exploratory in character and was based mostly on field survey data. Primary sources dominated the data, all of which was gathered using a standardized, structured questionnaire. Challenges in recruiting and keeping consumers have increased dramatically for India’s organized retail industry since the market opened to strong competition and the entry of private multinational firms.